Probable Tapentadol-Associated Serotonin Syndrome after Overdose. Issue 4 (April 2016) - Walczyk, Heather; Liu, Cheuk H. (Michael); Alafris, Antonia; Cohen, Henry
Purpose: Drug-induced serotonin syndrome is a potentially life-threatening condition. An Ovid MEDLINE, and PubMed search from 1950 to October 2015 revealed one published case report of suspected tapentadol-induced serotonin syndrome. We report a probable case of tapentadol-induced serotonin syndrome after overdose. Case Summary: A 48-year-old male was found unresponsive after a witnessed overdose of medications including tapentadol. After administration of naloxone by emergency medical services, the patient became combative and presented with altered mental status. He was managed with physical and pharmacologic restraints in the emergency department. Other medications that could be implicated in the patient's presentation include duloxetine and amitriptyline. It was suspected that the opioid properties of tapentadol were masking the patient's signs and symptoms of serotonin syndrome. The patient was admitted to the medical intensive care unit, remained stable, and was discharged 2 days later. Currently, there is one published case report of suspected tapentadol-induced serotonin syndrome after an overdose. The manufacturer of tapentadol reported no cases of serotonin syndrome during clinical trials, but there have been postmarketing cases reported with co-administration of other serotonergic drugs. Conclusion: We report a probable case of tapentadol-induced serotonin syndrome after overdose. Further research is needed to better understand the pharmacology and incidence behind this adverse event.